BENEFACTIVE VERBS IN DOUBLE OBJECT CONSTRUCTION (DOC) IN ENGLISH SENTENCES - Nia Kurniasih (Jurnal Sosioteknologi, 2009)
This study focuses on the syntactic and semantic features of the benefactive verbs in double object construction (DOC)in English sentences. A combination of various thoughts of linguists is used to serve as an eclectic theory employed in this research. This research uses the descriptive method with distributional techniques. The results of the research show the following. First, benefactive verbs assign three specific benefactive roles, namely beneficiary, recipient, and goal. Second, benefactive verbs come in two types of clauses, the double object construction (DOC) with a structure of (S + P/V + IO + DO) and the DOC with prepositions with the structure of (S + P/V + O + PREP + OP). Both constructions, in most cases, are licit, meaning each can be paraphrased into the other. The result, however, also shows that some constructions remain illicit, meaning the structure cannot be changed into the other one. Third, deeper semantic analysis shows that the verbs assigning the benefactive roles consist of two main types: 1) verbs that, in DOC, are followed by the preposition for and assign the beneficiary role. This type of verbs consists of verbs of 'make available' (MAva), verbs 'of creation' (VoCr), verbs 'of performance' (VPrf), verbs 'of preparation' (VPre), and verbs with idiomatic meanings (VIdi); and 2) verbs that, in DOC, have the preposition' to' before its object of preposition and assign the roles of recipient and goal. This type of verbs is classified into: verbs of caused movement (VCM), verbs of caused possession (VCP), and verbs of communication (VCOM) that bear two meanings: the kind of the communication device (VDev) and the transfer of message (VToM). Key words: ditransitive, benefactive, thematic role, beneficiary, recipient, goal